Antioxidant and pharmacological activity of Cucumis melo var. cantaloupe - Jorge, Neuza [UNESP]; Silva, Ana Carolinada; Veronezi, Carolina M. [UNESP] (Elsevier, 2022)
Cucumis melo L. is a worldwide appreciated fruit that offers multiple benefits to human health. However, besides the pulp, its by-products, such as peels and seeds, may also be used in the production of extracts and flours, and in the extraction of oils, since they contain phytochemicals of high nutritional and functional capacity. This chapter highlights the importance of using the by-products derived from C. melo L., especially from cantaloupe, as they present analgesic, antiinflammatory, antioxidant, anticancer, antimicrobial, diuretic, hepatoprotective, and immunomodulatory activities due to the presence of bioactive compounds. Also, their use may help minimize the environmental impact.
Keywords: Bioactive compounds; Melon; Oils; Peels; Seeds